Antibiotic prophylaxis of postoperative endophthalmitis after cataract surgery: results of the 2021 ASCRS member survey. Issue 1 (January 2022) - Chang, David F.; Rhee, Douglas J.
Abstract : Intracameral antibiotic prophylaxis for cataract surgery increased to 66% of ASCRS members and would increase to 93% if an approved antibiotic became commercially available. Moxifloxacin is the leading preference. Abstract : In an online survey of >1200 global cataract surgeons, 66% were using intracameral (IC) antibiotic prophylaxis. This compared with 50% and 30% in the 2014 and 2007 surveys, respectively. Irrigation bottle infusion and intravitreal injection was each used by only 5% of respondents. For IC antibiotics, vancomycin was used by 6% in the United States (52% in 2014), compared with 83% for moxifloxacin (31% in 2014). Equal numbers used compounded moxifloxacin or the Vigamox bottle as the source. There was a decrease in respondents using preoperative (73% from 85%) and postoperative (86% from 97%) topical antibiotic prophylaxis; the latter was not used by 24% of surgeons injecting IC antibiotics. Reasons cited by those not using IC antibiotics include mixing/compounding risk (66%) and being unconvinced of the need (48%). However, 80% believe having a commercially approved IC antibiotic is important; if reasonably priced, this would increase adoption of IC prophylaxis to 93%.